Conference Report: US FDA/EMA harmonization of their bioanalytical guidance/guideline and activities of the Global Bioanalytical Consortium. (February 2012) - Garofolo, Fabio; Michon, Josée; Leclaire, Virginie; Booth, Brian; Lowes, Stephen; Viswanathan, CT; Welink, Jan; Haidar, Sam; Teixeira, Leonardo de Souza; Tang, Daniel; Desilva, Binodh
The 2011 annual conference of the American Association of Pharmaceutical Scientists, held in Washington DC, USA, hosted a roundtable entitled: 'Update of the US FDA/European Medicines Agency (EMA) harmonization of their bioanalytical guidance – Global Bioanalytical Consortium activity and impact on small and large molecules.'' The roundtable was initiated with a presentation from CT Viswanathan on the history of the revision of the FDA guideline on bioanalytical method validation. It was followed by a presentation by Jan Welink who presented an update on the final European Medicines Agency guideline on bioanalytical method validation with relevance to ongoing harmonization efforts. The final presentation was by Fabio Garofolo on the progress of the Global Bioanalytical Consortium harmonization teams for small and large molecules. Brian Booth and Sam Haidar of the FDA updated the audience on the status of the revision of the FDA bioanalytical guidance. The roundtable was moderated by Stephen Lowes.